Pengembangan Media E-card Interaktif dalam Pelajaran IPAS Kelas III Sekolah Dasar Negeri 33 Cakranegara - Izzati Khairunnisa; Muhammad Tahir; Muhammad Sobri (Mataram University, 2026)
This study aimed to develop an interactive e-card media based on Augmented Reality (AR) for the science subject on “Vertebrate and Invertebrate Animals” for third-grade students at SDN 33 Cakranegara and to examine its feasibility in terms of validity and practicality. This study employed a Research and Development (R&D) approach using the ADDIE development model (Analyze, Design, Develop, Implement, and Evaluate). The research was conducted at SDN 33 Cakranegara with third-grade students as the research subjects. Data sources were obtained from material experts, media experts, teachers, and students. Data collection techniques included validation questionnaires, response questionnaires, and observation sheets. The data were analyzed descriptively using quantitative methods by converting percentage scores into feasibility categories. The interactive e-card media was developed through the five stages of the ADDIE model. The validation results showed a validity percentage of 95% from material experts and 93% from media experts, both categorized as highly valid. The practicality test results indicated teacher responses of 97% and student responses of 95%, supported by field observation data of 95%, all categorized as highly practical. Based on these findings, it can be concluded that the interactive e-card media is feasible for use as a learning medium in science education for third-grade elementary school students. Future studies are recommended to conduct effectiveness testing to measure the impact of the media on students’ learning outcomes.